Development of Hydrogen-Permselective Porous Membranes Using Radiation-Induced Graft Polymerization - Shin Hasegawa; Shinichi Sawada; Shinya Azami; Tokio Hagiwara; Akihiro Hiroki; Yasunari Maekawa (Quantum Beam Science, 2020)
Hydrogen-permselective membranes were developed using a radiation-induced grafting method. Styrene (St) and acrylic acid (AAc) monomers were introduced into porous polyvinylidene fluoride (PVDF) membranes to obtain St- and AAc-grafted PVDF membranes with grafting degrees of 82% and 92%, respectively. The porosities of the grafted membranes were controlled in the range 30–40% by hot-press compression at 159 °C and 4 MPa. The hydrogen permeability was found to be of the order of 10−7 mol/m2∙s∙Pa, which was higher than the permeability for water vapor and nitrogen (oxygen model). The St- and AAc-grafted membranes exhibited 9.0 and 34 times higher permeability for H2 than for H2O and N2, respectively.